Structural Components Of Communicative Competence - Makhmudova Nilufar Murotovna (Genius Journals, 2025)
This article examines the concept of competence, as well as the structural components of communicative competence such as motivational, axiological, informational and contentbased, and operational-activity-based. It provides a detailed analysis of the opinions of scientists on the development of communicative competence in future teachers
Keywords: competence; motivation; teacher